Planeación Estratégica para la Empresa "Pavi Chicken Loja", de la ciudad de Loja período 2015-2020 - Merino Palta, Fanny Valeria (2016)
This thesis called Strategic Planning for Business "Pavi Chicken Loja" city of Loja period 2015 - 2020, through its sections develops the strategic planning of the company named in order to design strategic objectives and plans action that achieve the mission and vision. Therefore, the strategic plan is based both on the general objective and specific objectives to follow, as they allowed the realization of the development of procedures, actions and analysis within the thesis exposed. Thus, the present plan developed is based on the construction of the mission, vision, objectives, company values and strategies proposed for the manager - owner of the restaurant, in order to let him know the weaknesses and shortcomings that currently have in your company. Therefore, with respect to the methodology concerning the development of this research, we worked with an interview directed to the manager - owner, as well as surveys addressed to employees and business clients, determining the results for the production of action plans that address the same decision-making of the company. Thus, within the investigative process it reaches completion by the initial diagnosis of "PAVI CHICKEN LOJA" that it lacks strategic planning and 5 business philosophy that allows grow before your competition. Likewise, no financial information has to meet the economic movements that are generated. Thus, it is recommended programming and design a record daily income and expenses. Finally, it is mentioned that this strategic plan proposes to establish the company as one of the best against its competitors, building a better future and obtaining the means to have excellent vision, adapting each of the members of the company to the changes that are generated in the same.